Leveraging Indonesian Values in Educational Service Marketing to Enhance Institutional Image - Hawu, Trisnawati L. Maramba; Ismanto, Bambang (Universitas Pendidikan Ganesha, 2024)
This study focuses on the issue of ineffective educational service marketing in enhancing the institution's image. The aim of this study is to analyze the implementation of educational service marketing, identify weaknesses in the applied marketing model, and explore aspects of Local Wisdom-Based Educational Service Marketing in improving the institution's image. This research uses a qualitative approach with an ethnographic design. The subjects of the study include the school principal, the vice principal for student affairs, cultural figures, and religious leaders. Data were collected through observations, in-depth interviews, document studies, and focus group discussions (FGD). Data analysis was performed using the model proposed by Miles and Huberman, which consists of three stages: data reduction, data presentation, and data verification. Data validation was conducted using triangulation techniques, including source triangulation and method triangulation. The results of the study indicate that the implementation of educational service marketing in this school has not been effective and has not been maximally executed. Identified weaknesses include the lack of structured marketing activities, insufficient use of local wisdom as an attraction in marketing, and a lack of understanding among school members regarding educational service marketing. Furthermore, local wisdom has not been optimally applied in every aspect of the marketing mix. The conclusion of this study is that efforts need to be made to maximize the implementation of educational service marketing by incorporating local wisdom into every aspect of marketing to enhance the institution's image.